PENYUSUNAN RENCANA BISNIS DAN UPAYA DIVERSIFIKASI PRODUK PADA USAHA MIKRO KERUPUK SUSMI SITUBONDO - Dyna Rachmawati; Adriana Anteng Anggorowati; Andrew Joewono; Anita Maya Sutedja; Farida Lianawati Darsono (Jurnal Abdi Insani, 2023)
Susmi Cracker Micro Business is located in the village of Curah Cottok, Kapongan District, Situbondo Regency, East Java. This micro business has been running its business since 2017. The main products produced are onion crackers, meatball crackers, and vegetable crackers. The crackers sold are still raw, packaged in plastic with a size of 1 kilogram. Susmi Crackers have succeeded in increasing their production volume, because of the technology supported from the Electrical Engineering Team of Widya Mandala Catholic Surabaya University (WMCSU). It impacts on the increase of the sales volume. Susmi Crackers is able to absorb labor, namely housewives in their villages to help cut the cracker dough. This encourages the Susmi Cracker to maintain and develop their business. The mothers who become the workforce are one of the motivations for these micro businesses to manage their businesses professionally. Therefore, the community engagement activity provides assistance to develop a business plan and helps Susmi Cracker to diversify products. This mentoring activity resulted in a business plan using a business model canvas, barbeque-flavored crackers, and Susmi Cracker knowledge in managing home industry distribution permits as well as negotiating skills with gift shops in the city of Situbondo.